Persuasive Elements within Indonesian Affiliate Marketing Content on Tiktok - Aditya Ihatra, Dzikri; Hasfi, Nurul; Surayya Ulfa, Nurist (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
This research investigates Indonesian affiliate marketing strategies on TikTok. Using content analysis, 25 successful affiliate videos were analysed through the lens of Jamieson's Electronic Eloquence Model. The findings confirm the model's effectiveness in identifying persuasive elements, with self-disclosure building rapport, conversational style enhancing authenticity, synoptics summarizing key information, and visual dramatization engaging viewers. Successful affiliates combine these elements, focusing on storytelling and visuals to drive persuasiveness. This study provides actionable insights for TikTok affiliates, emphasizing the importance of relatable content and strategic visual aesthetics.